2017
DOI: 10.1242/dev.151621
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-A and neuropilin 1 (NRP1) shape axon projections in the developing CNS via dual roles in neurons and blood vessels

Abstract: Visual information is relayed from the eye to the brain via retinal ganglion cell (RGC) axons. Mice lacking NRP1 or NRP1-binding VEGF-A isoforms have defective RGC axon organisation alongside brain vascular defects. It is not known whether axonal defects are caused exclusively by defective VEGF-A signalling in RGCs or are exacerbated by abnormal vascular morphology. Targeted NRP1 ablation in RGCs with a Brn3bCre knock-in allele reduced axonal midline crossing at the optic chiasm and optic tract fasciculation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 59 publications
3
38
0
Order By: Relevance
“…The distribution of axons and blood vessels plays an important role in development. When neuropilin 1 (NRP1) is knocked out of endothelial cells in a mouse model, there was abnormal formation of vessels in the optic nerve which lead to abnormal axon distribution (49). Normally the vessels line the outside of the axon bundle, however with this mutation the vessels are seen penetrating the axon bundles leading to exclusion zones where abnormal holes are found in the optic nerve.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of axons and blood vessels plays an important role in development. When neuropilin 1 (NRP1) is knocked out of endothelial cells in a mouse model, there was abnormal formation of vessels in the optic nerve which lead to abnormal axon distribution (49). Normally the vessels line the outside of the axon bundle, however with this mutation the vessels are seen penetrating the axon bundles leading to exclusion zones where abnormal holes are found in the optic nerve.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the latter, it has recently been reported that aberrant vessel patterning induced by loss of NRP1 signalling creates optic pathway holes because axons are excluded from areas of ectopic vessels (Erskine et al. ). Furthermore, in the mouse limb the pattern of vessels is determined by the sensory axonal pattern (Mukouyama et al.…”
Section: Resultsmentioning
confidence: 99%
“…What followed was a 25 year‐long journey seeking to understand how RGCs are instructed to project to one side of the brain or the other, in ‘normal’ pigmented and albino mice. In our review (Guillery et al ., ), Ray went on to say that ‘several candidate molecules have been identified in the retina and along the path of the axons, but to date no clearly defined role in the specific events of the pathway determination have been identified.’ While true in 1995, we now know a great deal about the cellular and molecular factors contributing to the path RGC growth cones take to lay down the binocular circuit (Petros et al ., ; Erskine et al ., ).…”
Section: Development Of the Ipsilateral And Contralateral Projectionmentioning
confidence: 97%
“…In fact, this consortium expressed on both growing axons and the terrain through which they grow, that acts synergistically for axon growth and guidance. Recently, other canonical and new guidance systems functioning in parallel have been reported for optic chiasm midline decussation (Erskine et al ., ; Peng et al ., ; Fig. ).…”
Section: Development Of the Ipsilateral And Contralateral Projectionmentioning
confidence: 99%